TINGKAT KEPUASAN PASIEN TERHADAP TENAGA KESEHATAN DALAM MEMBERIKAN LAYANAN DI PUSKESMAS MANDIANGIN KOTA BUKITTINGGI - Siti Mutia Kosassy; Adelse Prima Mulya; F. Yasmeardi (Jurnal Public Administration, Business and Rural Develoment Planning, 2020)
One of the quality health services from the health center can be measured by knowing patient satisfaction with the service. For Puskesmas Mandiangin Bukittinggi City, patient satisfaction is very important, considering the vision of this Puskesmas is to make Mandiangin District Health Center as a prime health service unit, equitable and affordable by the community to support the achievement of optimal health degrees. The purpose of this study was to determine patient satisfaction with the performance of health services at the clinic by measuring the level of patient satisfaction. This research is a descriptive study, to see a picture of patient satisfaction in the Mandiangin District Health Center which was conducted in August - October 2019. The population in the study was outpatients in the Puskesmas Mandiangin Bukittinggi District Health Center. The level of patient satisfaction was measured by the servqual method by conducting interviews with 73 patients at the public health center. Each statement was scored using the 1-4 Likert scale. In this study, the majority of respondents were satisfied with the service of health workers (doctors and nurses) at the public health clinic at Puskesmas Mandiangin (71.2%). The empathy dimension has a high percentage (75.3%). While responsiveness has a lower presentation compared to other dimensions (64.4%). The highest patient satisfaction value in each dimension namely; Nurse appearance (3.71), doctor's presence on time (3.71), nurse answers patient's questions clearly (3.64), patient believes in the medicine given by doctor (3.77) and doctor is able to communicate well with patients (3,81). Puskesmas Mandiangin needs to maintain and improve existing achievements. Some things that need to be taken into consideration to be further improved include the presence and skills of doctors at the clinic, the speed at which doctors solve problems, nurses 'experiences and nurses' attention to being good listeners.